Olfactory training is helpful in postinfectious olfactory loss: A randomized, controlled, multicenter study - Damm, Michael; Pikart, Louisa K.; Reimann, Heike; Burkert, Silke; Goektas, Oender; Haxel, Boris; Frey, Sabine; Charalampakis, Ioannis; Beule, Achim; Renner, Bertold; Hummel, Thomas; Huettenbrink, Karl-Bernd (Laryngoscope, 2014)
The aim of this study was to evaluate the effects of olfactory training (OT) on olfactory function in patients with persistent postinfectious olfactory dysfunction (PIOD).Randomized, single-blind, controlled, multicenter crossover study.Twelve tertiary university medical centers participated. Investigations were performed at three visits (baseline, after 18 weeks, and after 36 weeks), including only subjects with PIOD of <24-months duration. At each visit, participants received detailed assessment of olfactory function. Seventy subjects trained with high concentrations of four odors for 18 weeks; the other half (n = 74) trained with low concentrations of odors. For the following 18 weeks this regimen was switched.After 18 weeks, olfactory function improved in the high-training group in 18 of 70 participants (26%), whereas only 11/74 improved in the low-training group (15%). In subjects with a duration of olfactory dysfunction of <12 months, olfactory function improved in 15/24 participants (63%) of the high-training group and in 6/31 participants (19%) of the low-training group (P = .03).OT improves PIOD, and the use of odors at higher concentrations is beneficial to improvement. OT is a safe procedure and appears to be particularly useful in patients who start OT within 12 months after the onset of the disorder. OT is the first successful therapy regime in patients with PIOD.1b. Laryngoscope, 124:826-831, 2014.
EVALuna2:8511